2004
DOI: 10.1111/j.1365-2095.2004.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation of coated crystalline amino acids on growth performance and body composition of juvenile kuruma shrimp Marsupenaeus japonicus

Abstract: Supplementation of crystalline amino acids (CAA) in shrimp diets is unsuccessful in most cases. In the present study, various pre‐coated CAA were developed to minimize the leaching losses from diets in water and assessed using kuruma shrimp Marsupenaeus japonicus juveniles. Experimental diets were supplemented with coated CAA or non‐coated CAA to simulate the dietary amino acid profile to that found in the whole body protein of shrimp. The four diets contained CAA coated with either carboxymethyl cellulose (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 30 publications
8
60
0
Order By: Relevance
“…Water stability of the diet was estimated by the method of Fagbenro and Jauncey (1995) and found to be 96%. In addition to providing sufficient water stability, coating of crystalline L-amino acids also reduces the absorption rate of the amino acids (Cho et al 1992) and leaching (Alam et al 2004). We adopted this approach as a measure to prevent the leaching of crystalline amino acid from the test diets and optimize their use for protein gain.…”
Section: Methodsmentioning
confidence: 99%
“…Water stability of the diet was estimated by the method of Fagbenro and Jauncey (1995) and found to be 96%. In addition to providing sufficient water stability, coating of crystalline L-amino acids also reduces the absorption rate of the amino acids (Cho et al 1992) and leaching (Alam et al 2004). We adopted this approach as a measure to prevent the leaching of crystalline amino acid from the test diets and optimize their use for protein gain.…”
Section: Methodsmentioning
confidence: 99%
“…Optimal dietary lysine level has been quantified for some shrimp species, including P. monodon , Palaemonetes varians , and Penaeus uannamei (Akiyama ; Fox et al ; Millamena et al ; Palma et al ). Success in these experiments is partly attributed to the application of various techniques such as encapsulating or binding of diet ingredients to prevent leaching losses of CAAs (Alam et al ). For example, cellulose acetate phthalate, carboxymethyl cellulose (CMC), and κ‐carrageenan have been used to prevent leaching of CAAs from aquaculture feeds (Chen et al ; Millamena et al ).…”
mentioning
confidence: 99%
“…For example, cellulose acetate phthalate, carboxymethyl cellulose (CMC), and κ‐carrageenan have been used to prevent leaching of CAAs from aquaculture feeds (Chen et al ; Millamena et al ). Therefore, in the case of sea cucumber, it is important to incorporate specific binders that minimize leaching of CAAs from diets and ensure that essential nutrients are available to the organism (Alam et al ). Numerous studies have shown that dietary supplementation with lysine can improve growth, digestion, and immunity in fish or shrimp (Walton et al ; Xie et al , ).…”
mentioning
confidence: 99%
“…Alam, M., Teshima, S., Koshio, S., Ishikawa, M., 2004 Panserat, S., Ducasse-Cabanot, S., Plagnes-Juan, E., Srivastava, P., Kolditz, C., Piumi, F., Esquerre, D., Kaushik, S., 2008. Dietary fat level modifies the expression of hepatic genes in juvenile rainbow trout (Oncorhynchus mykiss) as revealed by microarray analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These amino acids were included at the highest concentrations in the EAA premix so this small initial peak may be a reflection of rapid uptake of free amino acids from the feed rather than an effect of Tau on metabolism of specific amino acids. Alam et al (2004) suggested that binding of crystalline amino acids within a matrix using caseingelatin could assist in negating this differential absorption and this may have been advisable in this case. Interestingly, this response was also seen in the plasma levels of the NEAA serine (Ser) which was not supplemented in the diet, so the reason for this fluctuation is not known.…”
Section: Discussionmentioning
confidence: 98%